Experiences of Professionals Working with Migrant Families who have Disabled Children - Sibeso Imbula Sveinsson 1970- (2020)
This qualitative study focuses on experiences of welfare service professionals working with migrant families who have disabled children aged 6 to 16 years. Five professionals who work with migrant families in diverse settings of the welfare service system participated in the study. The professionals are employed by Reykjavík City, are of different ages, and have a variety of professional backgrounds and work experience. The data was gathered through semi-structured interviews conducted in English, and each lasted for about 60 minutes. The findings reveal two main categories: the challenges encountered by the welfare service professionals working with migrant families and recommendations for improving services to meet needs of migrant families. Findings also indicate that miscommunication and misunderstandings are common in professional-family interactions, and the involvement of interpreters complicates matters. Professionals also indicate that migrant families face barriers in accessing information and services. Migrant parents also encounter many obstacles due to cultural differences, small networks and less access to information, resources and staff.